Polymorphism of the genetic diversity collections tomato greenhouse crops the resistance to fusarium wilt and other economic-biological characteristics: MESSAGE I. VARIANCE - Черненко, В. Л.; Семененко, І. І. (Scientific Progress & Innovations, 2012)
The article presented the results of studying the level of variability of complex traits of important collections of tomato greenhouses (Solanum lycopersicum L.). Genetic diversity of collection features 43 samples of four botanical subspecies. Theoretically proved and practically realized the possibility of successful selection of contrasting and stable on the basic parameters of forms (isolines) of the tomato. All of them are today used in the breeding program of this culture in heterosis.